Uncertainty, Everyday Mobility, and Urban Citizenship: Civic Storytelling of Public Transport Use in Surabaya, Indonesia - Dwi Prasetyo; Teguh Dwi Putranto; Ade Firmannandya (Jogjakarta Communication Conference (JCC), 2026)
Public transportation is often evaluated through technical indicators such as punctuality, coverage, affordability, and integration. However, these approaches do not fully capture how mobility is experienced in everyday urban life. This article examines how users of the Suroboyo Bus and Wira-Wiri Feeder services in Surabaya interpret and narrate their daily journeys, and assesses civic storytelling as an analytical lens for revealing the gap between transportation modernization policy narratives and the realities of use. This study employs an interpretive qualitative case study that combines phenomenological sensitivity, narrative inquiry, and contextual observation. Eight active users were interviewed in depth regarding their entire travel chain, from accessing the service to arriving at their destination. The findings indicate that uncertainty constitutes a central condition shaping everyday mobility experiences. User evaluations are not limited to in-vehicle experiences, but encompass stages of access, waiting, boarding, intermodal transfer, and arrival. Participants’ narratives are structured around five interrelated themes: distributed security, everyday adaptation, experienced accessibility, emotional burden, and the construction of citizenship. The most positive assessments are directed toward the bus interiors, while negative experiences are concentrated at the periphery of the system, particularly along access routes, waiting points, and transfer processes. This article argues that public transportation functions as an infrastructure of experience, emotion, and urban citizenship, and underscores the importance of more human-centered transportation evaluations that incorporate users’ lived experiences and narrative evidence.